1999
DOI: 10.1002/etc.5620180301
|View full text |Cite
|
Sign up to set email alerts
|

An integrated evaluation of the persistence and effects of 4‐nonylphenol in an experimental littoral ecosystem

Abstract: Abstract-A comprehensive littoral enclosure study was conducted to assess the persistence and distribution of 4-nonylphenol (NP) in a littoral ecosystem, and to evaluate the compound's effects on resident aquatic biota. Enclosures with a mean (ϮSD) surface area and volume of 31.4 Ϯ 3.3 m 2 and 32.0 Ϯ 6.4 m 3 , respectively, received eleven applications at 48-h intervals with one of four different rates of NP. This created a 20-d application period which was followed by a three to fourteen month observation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The distribution of nonylphenol in aquatic environment in several rivers in Europe and USA has been reported where it has been found to be mainly concentrated in sediment [3,5,[8][9][10]. Various studies have also confirmed that nonylphenol present risks to aquatic organisms, especially zooplanktons and benthic macro-invertebrates in areas of high chronic exposure to high concentrations [11,12]. They have so far been found to exert toxicity and estrogenic effects on aquatic organisms with attendant effects on human health [13].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of nonylphenol in aquatic environment in several rivers in Europe and USA has been reported where it has been found to be mainly concentrated in sediment [3,5,[8][9][10]. Various studies have also confirmed that nonylphenol present risks to aquatic organisms, especially zooplanktons and benthic macro-invertebrates in areas of high chronic exposure to high concentrations [11,12]. They have so far been found to exert toxicity and estrogenic effects on aquatic organisms with attendant effects on human health [13].…”
Section: Introductionmentioning
confidence: 99%
“…The chromatographic analyses of the synthesized reference compound and the metabolites led to their identification as 2(3,5-dimethyl-3-heptyl)-1,4-benzenediol. This finding indicates that the nonylphenol metabolism of this bacterium involves unconventional degradation pathways where an NIH shift mechanism occurs.Nonylphenol (NP) is a ubiquitous pollutant which mainly results from the biodegradation of widely used NP polyethoxylate surfactants, and it is well known for its endocrine systemdisrupting potential (5,8,11,13,20,21). NP is used as part of a technical mixture which consists of more than 20 branched isomers of the nonyl chain (23, 28).…”
mentioning
confidence: 99%
“…Nonylphenol (NP) is a ubiquitous pollutant which mainly results from the biodegradation of widely used NP polyethoxylate surfactants, and it is well known for its endocrine systemdisrupting potential (5,8,11,13,20,21). NP is used as part of a technical mixture which consists of more than 20 branched isomers of the nonyl chain (23,28).…”
mentioning
confidence: 99%
“…And the partition coefficient (log k P = 4.8) and the correlation (R 2 = 0.63) for SPM phase and water phase clearly indicated that NP was readily adsorbed to SPM and rapidly reach the equilibrium between water and SPM. Liber et al (1999) also demonstrated that once released into littoral zone of pond ecosystem, NP has a relatively short time in the water column but more persistent in sediment. And the short persistence in water column was apparently not a result of degradation but rather largely a sequence of the hydrophobic nature of NP leading to a partitioning to solid.…”
Section: Behavior Of Aps In Surface Water Along the Jialu Rivermentioning
confidence: 85%